Glaukoma Kongenital Primer: Tinjauan Pustaka - Safira, Maya; Gusti, Naufal (Cermin Dunia Kedokteran, 2026)
Primary congenital glaucoma is a form of glaucoma caused by abnormal development of the anterior chamber angle, particularly the trabecular meshwork, which obstructs aqueous humor outflow and leads to increased intraocular pressure. This condition is one of the leading causes of blindness in children and has long-term consequences on visual development and overall quality of life. More than 75% of primary congenital glaucoma cases are diagnosed within the first 12 months after birth; in more severe cases, the disease may already be detected at birth. Persistent elevation of intraocular pressure that is not promptly treated can result in permanent optic nerve damage, globe enlargement (buphthalmos), corneal edema and opacity, and progressive visual field defects. Diagnosis is generally established based on characteristic clinical features such as epiphora, photophobia, and blepharospasm, supported by comprehensive ophthalmologic examination. Surgical intervention remains the primary treatment approach, aiming to reduce intraocular pressure and prevent further complications. Early detection and timely management are essential to preserve visual function and prevent permanent visual impairment in affected children.